Justification of choice of corrosion-resistant material of blowout preventer body based on modeling of its elastic-plastic deformation - K. V. Syzrantseva; K. V. Kuskov; M. A. Pazyak (Омский научный вестник)
The paper considers a method for justifying the choice of a corrosion-resistant material for the manufacture of a blowout preventer body based on computer simulation of an elastic-plastic task in the ANSYS Mechanical APDL software. To describe the material properties, a multilinear deformation model is used, the reference points of which are calculated as a result of working out the macro developed by the authors based on two models: RambergOsgood and the “method of sequential corrections” proposed by TSAGI specialists. The paper presents the results of computer simulation on the loading of the PShKM-ASMT-114x21 preventer body by working and double starting pressure for four variants of body materials. The calculations confirmed the high safety factor of the body for the currently used 40X steel showed sufficient working capacity of corrosion-resistant steels 20X13 and 30XMA. However, a computer experiment detected very extensive zones and the level of plastic strains as a result of loading the body made of 12X18H10T steel with double starting pressure. The obtained results indicate that the investigated preventer can be manufactured in corrosionresistant versions K1 and K2, but for the execution of K3 it is necessary to develop a fundamentally different geometry of the body.